2016
DOI: 10.1007/s11104-016-2938-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and resistance of tobacco cultivars to the progression of bacterial wilt, caused by Ralstonia solanacearum

Abstract: Background and aims Resistant cultivars are one of the most effective control measures used against bacterial wilt, caused by the soilborne bacterium Ralstonia solanacearum. We aimed to determine the effect of temperature and resistance of tobacco varieties on bacterial wilt occurrence. Methods Five tobacco cultivars, with varying resistance levels, were inoculated and transferred to growth chambers at 10, 15, 20, 25, 30, and 35°C. The growth rate of R. solanacearum was also studied in culture at 10, 20, and 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…High-temperature forced ripening also reduces the yield and quality of tobacco leaves 18 . Temperature plays a predominant role in affecting the rate of soil carbon mineralization 19 , and tobacco’s resistance mechanisms are also temperature dependent 20 . In addition, the properties of tobacco leaves, such as biomass, leaf area, sugar, nicotine content, etc., are largely influenced by moisture factors 21 .…”
Section: Introductionmentioning
confidence: 99%
“…High-temperature forced ripening also reduces the yield and quality of tobacco leaves 18 . Temperature plays a predominant role in affecting the rate of soil carbon mineralization 19 , and tobacco’s resistance mechanisms are also temperature dependent 20 . In addition, the properties of tobacco leaves, such as biomass, leaf area, sugar, nicotine content, etc., are largely influenced by moisture factors 21 .…”
Section: Introductionmentioning
confidence: 99%
“…Differences in bacterial wilt resistance levels between the first and second trials were evident in accessions of S. anguivi, S. sisymbriifolium (SIS2), and S. torvum. The susceptibility or reduction of resistance in the second trial second could be due to the higher temperatures observed in the second trial, which reached 36 • C. Similar results were found in tomato and tobacco (Nicotiana tabacum), where resistant cultivars become susceptible when exposed to temperatures above 28 • C [26,45]. In addition, soil moisture and soil temperature may have influenced the resistance reaction of the genotypes [46].…”
Section: Discussionmentioning
confidence: 71%
“…Grafting onto resistant rootstocks could also provide an alternative solution to manage soil-borne pathogens, including bacterial wilt, in Solanaceous crops [24,25]. However, bacterial wilt resistance may vary with location, temperature, and strain differences of the pathogen [26]. Further identification of resistance sources to bacterial wilt for breeding, and introgression of resistance genes into eggplant rootstock/cultivar is the best strategy to improve the chances of durable resistance for managing bacterial wilt [2].…”
Section: Introductionmentioning
confidence: 99%
“…Our results are also in line with those of Singh et al [35] who evaluating the effect of temperature, cultivar and induced root wounding on virulence of R. solanacearum in greenhouse tomato crops, showed no wilt symptoms at 20˚C or lower. In addition, Bittner et al [36], breeding tobacco varieties resistant against R. solanacearum, reported the highest incidences when temperatures were between 30˚C and 35˚C and no symptoms at temperatures less than or equal to 15˚C. Oussou et al [16] also reported a high wilt rate of Solanum macrocarpum artificially inoculated with R. solanacearum during the dry period compared to the wet period.…”
Section: Discussionmentioning
confidence: 99%